Type 3 innate lymphoid cells are associated with a successful intestinal transplant. Issue 2 (21st July 2020) - Kang, Jiman; Loh, Katrina; Belyayev, Leonid; Cha, Priscilla; Sadat, Mohammed; Khan, Khalid; Gusev, Yuriy; Bhuvaneshwar, Krithika; Ressom, Habtom; Moturi, Sangeetha; Kaiser, Jason; Hawksworth, Jason; et al.
Abstract : Although innate lymphoid cells (ILCs) play fundamental roles in mucosal barrier functionality and tissue homeostasis, ILC‐related mechanisms underlying intestinal barrier function, homeostatic regulation, and graft rejection in intestinal transplantation (ITx) patients have yet to be thoroughly defined. We found protective type 3 NKp44 + ILCs (ILC3s) to be significantly diminished in newly transplanted allografts, compared to allografts at 6 months, whereas proinflammatory type 1 NKp44 − ILCs (ILC1s) were higher. Moreover, serial immunomonitoring revealed that in healthy allografts, protective ILC3s repopulate by 2‐4 weeks postoperatively, but in rejecting allografts they remain diminished. Intracellular cytokine staining confirmed that NKp44 + ILC3 produced protective interleukin‐22 (IL‐22), whereas ILC1s produced proinflammatory interferon‐gamma (IFN‐γ) and tumor necrosis factor‐alpha (TNF‐α). Our findings about the paucity of protective ILC3s immediately following transplant and their repopulation in healthy allografts during the first month following transplant were confirmed by RNA‐sequencing analyses of serial ITx biopsies. Overall, our findings show that ILCs may play a key role in regulating ITx graft homeostasis and could serve as sentinels for early recognition of allograft rejection and be targets for future therapies. Abstract : Analyses of the roles of distinct innate lymphoid cell subsets in human intestinal transplantation shows that protective type 3 innate lymphoid cells are associated with allograft health.